Description Of Family Support In Providing Exclusive Breastfeeding Postpartum Mother At The Pratama Widuri Clinic Sleman - Puspitasari, Riadinata Shinta; Adhisty, Yulia; Hartinah, Sri (Jurnal EduHealth, 2024)
Many breastfeeding mother still doubt that their breast milk will meet the baby's needs. Therefore, the role and support of the family (husband, parents, siblings) is needed in the continuation of breastfeeding (Suraeda, 2020). Family support is the external factor that has the greatest influence on the success of exclusive breastfeeding. The aim of this research is to determine the description of family support for postpartum mother in exclusive breastfeeding The method used was descriptive quantitative cross-section research design with a research sample of 32 respondents of postpartum mother who came to the Widuri Sleman Pratama Clinic selected using accidental sampling. The instrument used was the family support questionnaire from Ulfah Putri Utami. Data analysis in this study was univariate analysis. The results obtained by postpartum mother who received family support were 75.00%. At the age of 20-35 years as much as 90.63%. High school / vocational high school education as much as 84.38%. Multiparous mother were 59.38%. Mother who did not work were 71.88%.